Roll Away Saloon - Paulsen, Deirdre (Utah State University Press, 1985)
With his animated tales of Zane Grey, Butch Cassidy, and the Robbers Roost gang, Rider creates an engaging and believable picture of the joys and hardships of cowboy life.